2012
DOI: 10.1007/s00228-012-1291-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl reductase 1 expression influences daunorubicin metabolism in acute myeloid leukemia

Abstract: This pilot study suggests that CBR1 RNA expression may be helpful in identifying AML patients at risk of developing resistance or toxicity to daunorubicin due to increased formation of DOL. Further confirmation of these findings in a larger sample pool would be required to determine the applicability of these results. Inhibition of CBR1 can be an option to improve the efficacy and prevent toxicity related to the treatment. Influence of daunorubicin and DOL plasma levels on clinical outcome, if any, remains to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 33 publications
0
12
0
2
Order By: Relevance
“…The pivotal role of CBR1 is also supported by Plebuch et al where human pancreas carcinoma cells showed an increased resistance toward DAUN when transfected with cDNA coding for CBR1 [66]. Additionally, one clinical study showed that an increased expression of CBR1 significantly reduced the in vitro cytotoxicity of DAUN and was also positively correlated with intracellular DAUNOL levels in acute myeloid leukemia patients [67]. The latter even suggests that ''inhibition of CBR1 can be an option to improve the efficacy and prevent toxicity''.…”
Section: Discussionmentioning
confidence: 77%
“…The pivotal role of CBR1 is also supported by Plebuch et al where human pancreas carcinoma cells showed an increased resistance toward DAUN when transfected with cDNA coding for CBR1 [66]. Additionally, one clinical study showed that an increased expression of CBR1 significantly reduced the in vitro cytotoxicity of DAUN and was also positively correlated with intracellular DAUNOL levels in acute myeloid leukemia patients [67]. The latter even suggests that ''inhibition of CBR1 can be an option to improve the efficacy and prevent toxicity''.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, for this review, we will only briefly discuss their role in anthracycline metabolism. While AKRs and CBRs are both carbonyl reducing enzymes, this section focuses specifically on the carbonyl reductases CBR1 and CBR3 [41,42]. These enzymes are found in a wide variety of tissues with a very broad range of substrates.…”
Section: A) Carbonyl Reductases (Cbrs)mentioning
confidence: 99%
“…The two SNP in CBR1 are situated very close to each other on chromosome 21 and are in high linkage disequilibrium, explaining the similar results obtained for the two variants. 7 An important question when considering correlations of SNP with drug-induced toxicity is whether the polymorphisms actually impact on the expression level or functionality of the corresponding proteins. The effect of SNP on ABCB1 has been reviewed by Leschziner et al 12 Most studies concluded that there is no effect of rs2229109 (C1199A) on mRNA or protein expression.…”
Section: Letters To the Editormentioning
confidence: 99%
“…Lars P. Jordheim, 1,2,3 Vincent Ribrag, 4 Hervé Ghesquieres, 5 Sophie Pallardy, 6 Richard Delarue, 7 Hervé Tilly,8 Corinne Haioun, 9 Fabrice Jardin, 10 Delphine Demangel, 2,3 Gilles A. Salles 11 …”
unclassified